Diagnosis of SARS-CoV-2: Importance of understanding current methods - Jaramillo-Valverde, Luis (2021)
Currently, both in Peru and in other countries, we have a wide range of tests available for the identification of individuals infected with COVID-19 disease; however, do we know the advantages and limitations of each of them?